Comparison of Spiritual Experiences and Distress Tolerance between Women with Type 2 Diabetes and Healthy Counterparts: A Cross-Sectional Study - Maryam Amerifar; Anahita Khodabakhshi Koulayi; Akram Sanagoo (Golestan University Of Medical Sciences, 2019)
Background and objectives: Diabetes is one of the main causes of morbidity and mortality worldwide. Spiritual experiences and religious belief can reduce tension and improve physical and mental health in diabetic patients. The purpose of this study was to compare spiritual experiences and distress tolerance between women with type 2 diabetes and healthy counterparts in Tehran, Iran. Methods: This descriptive and cross-sectional study was carried out on 100 women with type 2 diabetes who were selected from the Ferdowsi Diabetes Clinic (Tehran, Iran) and 100 non-diabetic counterparts. The participants responded to the Daily Spiritual Experience Scale and the Distress Tolerance Scale. Data were analyzed with SPSS 19 using independent t-test. Results: The mean score of daily spiritual experiences in women with diabetes (61.35 ± 13.54) was significantly higher than that in the healthy counterparts (47.47 ± 12.57) (P<0.01). Also, the mean score of distress tolerance was significantly higher in women with type 2 diabetes (44.69 ± 12.58) than in the controls (39.85 ± 9.65) (P<0.01). Conclusion: The results of the study showed that spiritual experiences and distress tolerance can be effective in improving the quality of life of people with type 2 diabetes.